История одного города - Салтыков-Щедрин Михаил Евграфович (Правда, 1984)
Экземпляры: аб (реторконверсия) / Инвентарный номер: 11978 / Цена: 2.10 / Сис.шифр: Р1 / Авт.знак: С 16 / ГРНТИ: 17.82 / ББК: 84(2=411.2)1